A review of polymer composites and adhesives for aircraft landing gear applications - Caglar, Hasan; Ayre, David; Mills, Andrew; Xu, Yigeng; Skote, Martin (MDPI, 2025)
This review paper explores the transformative potential of polymer composites and adhesives in reducing the weight of aircraft landing gear, thereby improving fuel efficiency and lowering emissions. The replacement of conventional metallic materials and mechanical fastenings with advanced thermoset/thermoplastic composites and adhesives can significantly enhance durability and performance in demanding operational environments. Unlike traditional fastening methods, the structural adhesives eliminate the weight penalties associated with mechanical fasteners, offering a lighter and more reliable solution that meets the rigorous demands of modern aerospace engineering. Furthermore, the review highlights a variety of manufacturing techniques and innovative materials, including bio-based polymers, self-healing materials, noobed composites, helicoid composites, and hybrid composites. The use of thermosets and vitrimers in adhesive bonding are presented, illustrating their ability to create robust and durable joints that enhance the structural integrity of landing gear systems. The paper also addresses current challenges, including recycling limitations and high material costs. Sustainability considerations, including the integration of self-healing materials, structural health monitoring systems, and circular economy principles, are discussed as essential for aligning the aerospace sector with global climate goals.
This article belongs to the Section Aeronautics
Keywords: 40 Engineering; 4016 Materials Engineering; 12 Responsible Consumption and Production; 4001 Aerospace engineering; landing gear; composite; adhesive; structural integrity; sustainability